Subject Review: The State of the Art in Integration of Cost and Time Models - Nabil Dmaidi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Cost and time are interdependent by their very nature. However, cost and time are generally treated in isolation both informally and within the terms of the contract. In reality, cost and time interact throughout the construction cycle. Thus, cost and time models and modelling systems must facilitate the integration of cost with time. Recognition must also be given to the need to integrate cost and time, and suitable contractual procedures for utilising more advanced styles of modelling must be implemented. In this paper traditional and emerging models of cost and time are reviewed and the contractual context of cost and time integration is explored. This review seeks to ascertain if and why models and contracts have failed to satisfy this particular requirement, as well as the other requirements placed upon them. Key Words: Cost Models; Time Model; Integration and Modelling System